Effects of locus bean gum, kappa carrageenan and iota carrageenan on the syneresis, texture and some sensory characteristics of cooked ham / efecto de la goma de algarrobo, la carragenina kappa y la carragenina iota sobre la sinéresis, textura y algunas c (2013)
The current study evaluated the effect of the additionof locus bean gum (LBG), Kappa carrageenan (KC) and Iotacarrageenan (IC) on some characteristics of cooked ham. For this purpose, a 2% mixture of LBG: KC: IC was added to the formula of a cooked ham standard brine, established according to the following ratios of 14 treatments (T): (T1): 100% IC; (T2): 100% KC; (T3): 50: 50 LBG: KC mixture; (T4): 50: 50 LBG: IC mixture; (T5): 33.33: 66.67KC: IC mixture; (T6): 66.67: 33.33 KC: IC mixture; (T7): 25: 75 LBG: KC mixture; (T8): 25: 75 LBG: IC mixture; (T9): 50: 16.17: 33.33 LBG: KC: IC mixture; (T10): 50: 33.33: 16.17 LBG: KC: IC mixture; (T11): 25: 56.25: 18.75 LBG: KC: IC mixture; (T12): 25: 18.75: 56.25 LBG: KC: ICmixture; (T13): 12.5: 43.75: 43.75 LBG: KC: IC mixture and (T14): 37.5: 31.25: 31.25 LBG: KC: IC mixture. For all brines, the cooked ham was prepared and extended to 100%, and characteristics of hardness and elasticity were evaluated 14 and 28 days after manufacturing, through a texture analysis profile (TAP); along with syneresis in the packaging (purges) by gravimetric analysis and, hardness, elasticityand general appearance; and sensory attributes through a sensory analysis. The lowest syneresis was shown for T11 and the lowest predicted syneresis by a third grade polynomial was shown in the mixtures 18.12: 64.46: 17.42 and 16.36: 65.56: 18.08 of LBG: KC: IC for days 14 and 28, respectively, with a syneresis value of 0.88%and 2.83%; the highest instrumental hardness (TAP) was found inT7, and the highest predicted hardness at 14 days was found in mixture 24.72: 75.28 of LBG: KC, with a value of 22.74 N, while the highest predicted elasticity coinciding with a high hardness region was found in mixture 26.21: 67.82 : 8.98 of LBG: KC: IC, with a value of 0.93. In the sensory analysis, T7 and T11 (sampling points closer to these optimal) were those that received the best scores in the evaluated parameters.